Asthma Severity and Control and Their Association With Perinatal Mental Illness. (February 2022) - Aker, Amira M.; Stephenson, Anne L.; Wilton, Andrew S.; Vigod, Simone N.; Dennis, Cindy-Lee; Guttmann, Astrid; Brown, Hilary K.
Objective: Growing evidence suggests asthma increases perinatal mental illness risk, but few studies have explored the impact of asthma severity and control. Our objective was to explore the association between asthma severity and control and perinatal mental illness risk and the impact of asthma exacerbations during pregnancy on postpartum mental illness risk. Methods: This was a population-based retrospective cohort study of all women in Ontario, Canada, from 2005 to 2015 with a singleton live birth who used public drug insurance, excluding women with recent history of mental illness. We constructed modified Poisson regression models to assess the risk of perinatal mental illness, defined as a mood or anxiety, psychotic or substance use disorder, self-harm or other mental illness diagnosed from conception to 365 days postnatally. Models controlled for socio-demographic factors and medical history. Results: There were 62, 583 women in the cohort (46.7% between 15 − 24 years), of whom 22.7% had asthma (94.3% mild, 5.7% moderate/severe; 86.5% controlled and 13.5% uncontrolled). After adjustment, there was increased risk of perinatal mental illness with mild asthma (adjusted relative risk [RR]: 1.12; 95% confidence interval [CI], 1.09 to 1.16) and moderate/severe asthma (aRR: 1.16; 95% CI, 1.04 to 1.30) compared to no asthma. Controlled asthma (aRR: 1.11; 95% CI, 1.08 to 1.15) and uncontrolled asthma (aRR: 1.19; 95% CI, 1.11 to 1.27) were also associated with increased perinatal mental illness risk compared to no asthma. Women with worsened asthma during pregnancy had the highest risk of postpartum mental illness compared to no change in asthma status (by severity: aRR: 1.57; 95% CI, 1.36 to 1.80; by control: aRR: 1.37; 95% CI, 1.22 to 1.54). Conclusion: Asthma is associated with increased risk of perinatal mental illness, particularly in the presence of asthma exacerbations in pregnancy. The results support multidisciplinary collaborative care programmes throughout the perinatal period, especially among women with asthma exacerbations during pregnancy.